2013
DOI: 10.1016/j.aap.2013.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Older drivers’ opinions of criteria that inform the cars they buy: A focus group study

Abstract: Safe driving in older adulthood depends not only on health and driving ability, but on the driving environment itself, including the type of vehicle. However, little is known about how safety figures into the older driver's vehicle selection criteria and how it ranks among other criteria, such as price and comfort. For this purpose, six focus groups of older male and female drivers (n=33) aged 70-87 were conducted in two Canadian cities to explore vehicle purchasing decisions and the contribution of safety in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
(38 reference statements)
1
14
0
Order By: Relevance
“…Koppel, Clark, Hoareau, Charlton, and Newstead (2013) found that price was identified as most important (43%) among consumers aged 65 and older, yet half of those surveyed still ranked a safety-related feature (e.g., antilock brakes) in the top spot from a predefined list of features. This result is similar to findings from focus groups conducted with older drivers (aged 70 to 90) where participants emphasized the importance of certain safety features (i.e., seat belts, air bags, braking) but downplayed its impact on their vehicle purchase (Zhan et al, 2013). Most participants in the focus groups admitted they were unfamiliar with their car’s safety rating at the time of purchase.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Koppel, Clark, Hoareau, Charlton, and Newstead (2013) found that price was identified as most important (43%) among consumers aged 65 and older, yet half of those surveyed still ranked a safety-related feature (e.g., antilock brakes) in the top spot from a predefined list of features. This result is similar to findings from focus groups conducted with older drivers (aged 70 to 90) where participants emphasized the importance of certain safety features (i.e., seat belts, air bags, braking) but downplayed its impact on their vehicle purchase (Zhan et al, 2013). Most participants in the focus groups admitted they were unfamiliar with their car’s safety rating at the time of purchase.…”
Section: Discussionsupporting
confidence: 82%
“…In a survey of over a thousand older drivers (aged 60 to 79) in Great Britain, Herriotts ( 2005 ) found that vehicle entry (33%) and exit (27%) is the most signifi cant challenge in terms of vehicle design followed by visibility, particularly with regard to seeing out the rear window when reversing the vehicle. Problems with vehicle accessibility as well as visibility and adjustability have also been identifi ed in a series of focus group studies with older drivers (Shaw, Polgar, Vrkljan, & Jacobson, 2010 ;Vrkljan et al, 2010 ), including a more recent investigation that examined factors that infl uenced their vehicle purchase (Zhan, Porter, Polgar, & Vrkljan, 2013 ). Older drivers report that ingress and egress diffi culties are associated with declining strength and balance, as well as design of the vehicle itself such as the size of the door opening, low seats, raised sills, and the lack of handles to support safe entry and exit from their respective vehicle (Shaw et al, 2010 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that car designers and engineers need to pay particular attention to the ease of entry and exit for several reasons. This is firstly because vehicle entry is the initial interaction the customer has with the vehicle and is a key influence on purchasing decision (Causse et al, 2012;Tetlock, 1983;Zhan et al, 2013). Secondly, entry and exit requires attention due to the number of problems drivers have getting in and out of cars.…”
Section: Introductionmentioning
confidence: 99%
“…Line-of-sight 1 to the external environment, which is sometimes referred to as driver visibility, has been identifi ed as a key area in which older drivers experience problems that can affect their operation of a motor vehicle (Charlton, Fildes, & Andrea, 2002 ;Eby & Molnar, 2012 ;Zhan, Porter, Polgar, & Vrkljan, 2013 ). A survey of older drivers indicated that most respondents (74%) attributed problems with line-ofsight to limitations in their neck mobility (Herriotts, 2005 ).…”
mentioning
confidence: 99%